B-seco limonoids from the bark of Toona ciliata. (December 2020) - Bu, Yunge; Zhang, Panpan; Li, Ying; Tang, Pengfei; Zhang, Wenyan; Luo, Jun; Kong, Lingyi
Graphical abstract: Highlights: Five new B- seco limonoids (1-5 ), along with five known compounds (6-10 ) were isolated from the bark of Toona ciliata Roem. Their B- seco frameworks featured a ε -7(8)-lactone, 1, 14-oxygen bridge, or 1, 11-oxygen bridge. Compound 1 exhibited significant anti-inflammatory activity. Abstract: Toonayunnanaes A-E (1 -5 ), five B- seco limonoids, along with five known compounds (6-10 ) were isolated from the bark of Toona ciliata. Compound 1 is a limonoid with a ε -7(8)-lactone in the B ring, and compound 2 possesses a 1, 14-oxygen bridge and a 15-OH. Their structures were elucidated by extensive spectroscopic analysis including 1D and 2D NMR, and HRESIMS. Compound 1 exhibited significant inhibition effect of NO production in LPS-stimulated RAW264.7 macrophages with an IC50 value of 10.94 ± 0.08 μM.